Etos Kerja Pedagang Kaki Lima Masyarakat Pantai Bahari Polewali Mandar: Work Ethic of Street Vendors in the Polewali Mandar Beach Community - Nurnaningsih, Nurnaningsih; Sappeami, Sappeami; Hassanuddin, Hassanuddin (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
This research is motivated by the importance of work ethic in supporting the success of street vendors (PKL), particularly in the tourism area of Bahari Beach, Polewali Mandar. The purpose of this study is to examine the work ethic of PKL by focusing on work attitude, discipline, honesty, and responsibility, as well as the factors that influence it. The study employs a descriptive qualitative approach through observation, and documentation. Informants were selected purposively. Data analysis includes reduction, presentation, and conclusion drawing, with validity tested through triangulation. The findings show that PKL at Bahari Beach possess a good work ethic. They work with enthusiasm, maintain discipline in trading hours, practice honesty in pricing, and take responsibility for cleanliness and order. Influencing factors include social and cultural values, economic needs, religious beliefs, experience, and business environment conditions.